Low temperature CVD growth of WSe2 enabled by moisture-assisted defects in the precursor powder. (1st October 2022) - Sassi, Lucas M; Krishnamoorthy, Aravind; Hachtel, Jordan A; Susarla, Sandhya; Apte, Amey; Castro-Pardo, Samuel; Ajnsztajn, Alec; Vajtai, Robert; Vashishta, Priya; Tiwary, Chandra Sekhar; Puthirath, Anand B; Ajayan, Pulickel M
Abstract: Two-dimensional transition metal dichalcogenides (TMDs) have been proposed for a wide variety of applications, such as neuromorphic computing, flexible field effect transistors, photonics, and solar cells, among others. However, for most of these applications to be feasible, it is necessary to integrate these materials with the current existing silicon technology. Although chemical vapor deposition is a promising method for the growth of high-quality and large-area TMD crystals, the high temperatures necessary for the growth make this technique incompatible with the processes used in the semiconductor industry. Herein, we demonstrate the possibility of low-temperature growth of TMDs, using tungsten selenide (WSe2 ) as a model, by simply using moisture-assisted defective tungsten oxide (WO3 ) precursor powders during the growth of these materials. Density functional theory calculations reveal the mechanism by which moisture promotes the defect formation on the precursor crystal structure and how it dictates the reduction of the temperature of the growth. The results were compared with the standard growth at high temperatures and with a precursor mixture with alkali salts to show the high quality of the WSe2 grown at temperatures as low as 550 °C. To conclude, the work improves the understanding of nucleation and growth mechanisms of WSe2 at low temperatures and provides a useful strategy for the growth of TMDs at temperatures required for the back-end-of-line compatibility with current silicon technology.